Modeling Green Customer Loyalty in Sustainable Hospitality: The Mediating Role of Customer Satisfaction in Green Hotels in Yogyakarta - Nining Yuniati; Alfatika Citra Rahadevi (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines the formation of green customer loyalty in sustainable hospitality, particularly in green hotels. Despite increasing environmental awareness among consumers, green hotels often face a paradox of perceived lower comfort and higher prices. This raises questions about whether environmentally conscious customers truly become loyal and what mechanisms drive such loyalty. Design/methodology/approach – This research employs a quantitative approach using survey data collected from 153 hotel guests in Yogyakarta, Indonesia. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the relationships between green purchase decisions, customer satisfaction, and customer loyalty, including the mediating effect of satisfaction. Findings/Results – The results show that green customer loyalty is not directly influenced by green purchase decisions but is fully mediated by customer satisfaction. This indicates that environmental awareness alone is insufficient to generate loyalty without a satisfying service experience. Originality/Value – This study proposes a value–experience–loyalty framework, highlighting customer satisfaction as the key mechanism linking environmental values to loyalty. The findings contribute to the literature by clarifying the indirect formation of green loyalty and provide managerial implications for designing meaningful and engaging green service experiences to enhance customer retention.